The theatre of nation Irish drama and cultural nationalism, 1890-1916 - Levitas, Ben, Dr (Oxford historical monographs., 2002)
What role did the theatre of the Irish literary revival play in the politics of identity debated in pre-revolutionary Ireland? Conversely, how far did that debate influence the development of the theatre? Ben Levitas pursues such questions through a study of Irish drama and the nationalist debate.